Impact of deployment of “Stork Network” in hospitalizations in the Neonatal Intensive Care Unit - Sandra Mara Aparecida dos Santos de Andrade; Cristiana Aparecida Soares Manzotti; José Alípio Garcia Gouveia; Cristiane Faccio Gomes; Marcelo Picinin Bernuci; Angélica Capellari Menezes Cassiano (Rev Rene)
Objective: to assess the impact of the deployment of “Stork Network” (Rede Cegonha) in hospitalizations in the Neonatal Intensive Care Unit. Methods: a retrospective cross-sectional study with 283 medical records of newborns hospitalized in neonatal intensive care unit before and after the implementation of Stork Network, correlating data from pregnant women with the babies’ conditions. Results: after the implementation of Stork Network, the percentage of pregnant women who performed six or more visits to the hospital increased 6.5% and the diagnosis of hypertensive disorders of pregnancy reduced 10.8%. It was also noted reduction of one week in the mean gestational age of babies and 14.4% reduction in the percentage of babies weighing ≥2500 grams. The number of deaths during hospitalization increased from 2.4% to 14.5%. Conclusion: the goal of performing screening and monitoring of risk pregnancies was reached, however, the reduction of neonatal mortality rate is still challenging.